Targeting Abnormal Tau Phosphorylation for Alzheimer’s Therapeutics - Singh, Aditya; Ansari, Vaseem Ahamad; Mahmood, Tarique; Hasan, Syed Misbahul; Wasim, Rufaida; Maheshwari, Shubhrat; Akhtar, Juber; Sheikh, Suvaiv; Vishwakarma, Vishal Kumar (Hormone and Metabolic Research, 2024)
Alzheimer’s disease (AD) is a widespread neurodegenerative disorder characterized by progressive memory and cognitive decline, posing a formidable public health challenge. This review explores the intricate interplay between two pivotal players in AD pathogenesis: β-amyloid (Aβ) and tau protein. While the amyloid cascade theory has long dominated AD research, recent developments have ignited debates about its centrality. Aβ plaques and tau NFTs are hallmark pathologies in AD. Aducanumab and lecanemab, monoclonal antibodies targeting Aβ, have been approved, albeit amidst controversy, raising questions about the therapeutic efficacy of Aβ-focused interventions. On the other hand, tau, specifically its hyperphosphorylation, disrupts microtubule stability and contributes to neuronal dysfunction. Various post-translational modifications of tau drive its aggregation into NFTs. Emerging treatments targeting tau, such as GSK-3β and CDK5 inhibitors, have shown promise in preclinical and clinical studies. Restoring the equilibrium between protein kinases and phosphatases, notably protein phosphatase-2A (PP2A), is a promising avenue for AD therapy, as tau is primarily regulated by its phosphorylation state. Activation of tau-specific phosphatases offers potential for mitigating tau pathology. The evolving landscape of AD drug development emphasizes tau-centric therapies and reevaluation of the amyloid cascade hypothesis. Additionally, exploring the role of neuroinflammation and its interaction with tau pathology present promising research directions.
Keywords: Alzheimer’s disease; phosphorylation; tau; GSK-3β; CDK5